The Use Of Simulation And Role-Play In Enhancing Speaking Skills In Learning English Language - Noraisah Nurul Fatwa, Mohd Razali; Rosnani, Ismail (Journal of Education and Social Science (JESOC), 2017)
Simulation and role-play are among the activities that can promote speaking skills. This study shed light on both the relation of the use of simulation and role-play in enhancing the student’s speaking skills and its benefits to the students. It is also focuses on the student’s perception towards the use of simulation and role-play in the classroom in helping them increasing their speaking skills. For the achievements of these purposes, 40 students of Form 2A from Sekolah Agama Menengah (SAM) Muhammadiah, Sabak Bernam were involved in completing the performance test and questionnaires. To enhance the quality of the data collected, the observation was also used to help the researcher examine the natural behaviour of the students and provides more details to the findings. The result of this study shows many positive signs in the students because they enjoyed the simulation and role-play activities. This study support that through simulation and role -play, teachers can help their students improve their speaking skills and bring positive changes in the class as well. Students were exposed to communication practices the same as they face real-life situations. They also practiced new vocabulary which help in enhancing their fluency.